Implementation of digital marketing at the Grand Kutilang Syariah Hotel Bandar Lampung during the recovery period after the Covid-19 pandemic: A sharia business perspective - Fauziyah, Asfiatul; Anggraeni, Erike; Hilal, Syamsul (Universitas Islam Indonesia, 2023)
IntroductionPrevious studies have analyzed the application of digital marketing in the hotel industry during the Covid-19 pandemic. However, research on digital marketing in the context of the hotel industry with an Islamic approach is still limited.ObjectivesThis study discusses the implementation of digital marketing in a sharia hotel as response to the Covid-19 pandemic. MethodThis study used a qualitative approach with a case study at Grand Kutilang Syariah Hotel Bandar Lampung. Data collection was carried out using questionnaires, and data analysis was carried out using inductive technique.ResultsThe Grand Kutilang Sharia Hotel, as part of tourism and hospitality industry in Lampung Province, employed digital marketing strategies to maintain business continuity during and after the COVID-19 pandemic. The implementation of digital marketing in The Grand Kutilang Sharia Hotel during the Covid-19 pandemic, involves optimizing the use of social media platforms such as WhatsApp, Instagram, Facebook, Twitter, YouTube, and TikTok. This implementation aligns with Sharia business principles.ImplicationsThis study shows the importance of adopting technological advancement in sharia hotel industry. Sharia hotels should take advantage of technological developments to maintain their business.Originality/NoveltyThis study contributes to the literature regarding sharia hotel marketing strategies in facing the crisis.